An analysis of innovation competitiveness of China through patent analysis - Lei, Xiao-Ping; Chen, Dar-Zen; Huang, Mu-Hsuang; Zhao, Zhi-Yun; Zhang, Xu; Zheng, Jia; Zhao, Yun-Hua; Zhang, Ze-Yu; Liu, Run-Sheng (Malaysian Journal of Library and Information Science, 2017)
Lei, X. P., Chen, D. Z., Huang, M. H., Zhao, Z. Y., Zhang, X., Zheng, J., ... & Liu, R. S. (2012). An analysis of innovation competitiveness of China through patent analysis.Â Malaysian Journal of Library & Information Science,Â Vol.17, no. 2:Â 17-32. This article assesses the innovation competition characteristics in China through patent analysis. TheÂ Chinese patents in US Patent and Trademark Office (USPTO) database from 2004 to 2008 are used forÂ analysis. The findings suggest that the innovation competitiveness of China has increased in recentÂ years. The absolute number of patents has shown the trend of rapid growth, but the share of utilityÂ patents is much lower than the global share. Based on analysis of technology fields, two main highÂ innovation technology fields of China are the Electrical and Electronic machinery (E&E) andÂ Computer and Communication (C&C) fields. The main international technology cooperation partnerÂ in these two fields is Taiwan. Moreover, Chinese patent output in the US is concentrated on a fewÂ large enterprises, and the patent proportions of the top 5, 15 and 30 assignees have increased eachÂ year. The top 5 patent assignees demonstrate strong innovation competitiveness in C&C and E&EÂ fields. Among the large assignees are Hong Fu Jin Precision in both E&E and C&C fields, and Fu ZhunÂ Precision and Huawei Technologies in E&E and C&C field respectively